Age group differences on perception of autoplay in mobile game playing among korean gamers - Doo Heon Song; Seunghun Lee (Institute of Advanced Engineering and Science, 2020)
Autoplay functions are embedded in most mobile role playing games and mobile multiplayer online battle arena games recently. Theoretically, there are different views on autoplay function in that it may be a ‘fake play’ from the traditional view and it is economical and gives functional benefits for game developing companies on balancing from functionalists’ view. In this paper, we investigate how this autoplay functions are perceived to the Korean mobile gamers. We report that there exists a strong age group effect on it and age 25 is the inflection point. Among 304 subjects including 69 females participated in this survey, the positive perception rate is positively proportional to the age from 36% to 73%. The reasons they choose to play autocombat function are convenience and utilizing sack times but the older groups (over 30) emphasize playing while doing other personal doings. Those who do not use autoplay function sustain the traditional view of game playing in that autoplay is ‘not’ the real game playing and there exists an age effect in that the inclination rate of autoplay function is negatively proportional to the age.